Recent Trends in the Optimal Renewable Power Dispatch Frameworks in Renewable Energy-Reliant Power Systems - Oba-Sulaiman, Z.; Adetona, S. O.; Alayande, A. S.; Balogun, A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2025)
This study presents a comprehensive survey of Optimal Renewable Power Dispatch (ORPD) frameworks in grid-rich renewables. The work employs comparative, and trend approaches to analyze optimization methods for ORPD of 61 relevant studies published from 2018 to 2024 by making use seven parameters emerged from the overall studies include voltage stability, carbon footprint, active power, reactive power, power loss, congestion, and energy storage. The results were tabulated using bibliometric tables, trend analysis, charts, and figures. The results show that previous research mainly emphasized minimizing economic cost through active power and loss optimization. However, voltage stability and congestion constraints were rarely integrated into the optimization framework simultaneously. Despite this, most studies remain focused on tackling these issues individually, where voltage stability is usually treated as a minor constraint, loss minimization is framed as a separate objective, and congestion management is approached through standalone mechanisms. While some integrated frameworks exist, they often address a limited scope of objectives, resulting in omissions in the development of comprehensive models. To close this significant research gap, there is need for the development of robust, multi-objective, and computationally efficient frameworks that holistically address these intertwined issues. The findings will therefore have academic, technical, and practical relevance, offering both theoretical contributions and actionable solutions for future power system planning and operation.